Effect of Return on Equity (ROE) and Earning Per Share (EPS) on the stock price of companies that are members of the infobank15 index on the Indonesia stock exchange - Sahlan, Hamdan; Syaroni, Deden Abdul Wahab (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
One of the approaches taken to predict stock prices was the fundamental approach. The problem raised in this study is the effect of Return On Equity (ROE) and Earning Per Share (EPS) on Stock Prices. This research was conducted with the aim to find evidence whether Return On Equity (ROE) and Earning Per Share (EPS) affect Stock Prices partially and simultaneously. This study uses data from companies that were included in the Infobank15 Index on the Indonesia Stock Exchange during certain period. The method used in this research was quantitative research methods. The analysis design used was multiple regression analysis, correlation analysis coefficient, and determinant analysis coefficient. Hypothesis testing using t-test and f-test. The results showed that partially Return on Equity (ROE) affected Stock Prices and Earning Per Share (EPS) affected Stock Prices. Simultaneously, Return On Equity (ROE) and Earning Per Share (EPS) had a significant effect on Stock Prices. The implication of this research is to provide input to investors in analyzing Stock Prices.